The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11409-020-09257-1
|View full text |Cite
|
Sign up to set email alerts
|

Measures of relative metacognitive accuracy are confounded with task performance in tasks that permit guessing

Abstract: This article investigates the concern that assessment of metacognitive resolution (or relative accuracy—often evaluated by gamma correlations or signal detection theoretic measures such as da) is vulnerable to an artifact due to guessing that differentially impacts low as compared to high performers on tasks that involve multiple-choice testing. Metacognitive resolution refers to people’s ability to tell, via confidence judgments, their correct answers apart from incorrect answers, and is theorized to be an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 70 publications
3
15
0
Order By: Relevance
“…As a consequence of the study, it can be assumed that metacognitive control and monitoring processes raise the task-related and topical accuracy. This confirms findings by Vuorre and Metcalfe [81] (p. 19) and Dunlovsky et al [74] (pp. 23-27) on the connection of metacognitive competences and the precision or matching of the task processing or learning success, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As a consequence of the study, it can be assumed that metacognitive control and monitoring processes raise the task-related and topical accuracy. This confirms findings by Vuorre and Metcalfe [81] (p. 19) and Dunlovsky et al [74] (pp. 23-27) on the connection of metacognitive competences and the precision or matching of the task processing or learning success, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The metacognitive knowledge and strategies are to be activated, organized, and verbalized by means of an action plan and thus be made available for the task-solving process [93] (pp. [79][80][81][82][83]. The method's targets are increasing problem comprehension, activating prior knowledge, and bringing to mind action steps during the problem-solving process.…”
Section: Methods Of Promoting Metacognitive Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon may be dependent on whether the MC measure being used is clearly integrated with the material being learned. Vuorre and Metcalfe (2021) noted that if academic tests are used that permit guessing (e.g. multiple-choice tests), for example, then "metacognitive misses" (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies reported no association between metacognitive monitoring and cognitive ability such as memory strategies (Kelly et al, 1976), text comprehension skills (Griffin et al, 2009). It has been suggested that these results may be attributed to the use of metacognitive indexes which are susceptible to the confounding effects of confidence bias, participants' level of type-1 performance and methods that permit guessing, which can differentially affect the estimation of metacognitive accuracy in high vs poor performers (Vuorre & Metcalfe, 2021). In the present study, we used a bias free signal detection theoretic framework,…”
Section: Discussionmentioning
confidence: 98%